Correction: The effect of crystallinity on the surface modification and optical properties of ZnO thin films. Issue 28 (8th July 2020) - Purbayanto, Muhammad Abiyyu Kenichi; Chichvarina, Olga; Ding, Jun; Rusydi, Andrivo; Darma, Yudi
Abstract : Correction for 'The effect of crystallinity on the surface modification and optical properties of ZnO thin films' by Muhammad Abiyyu Kenichi Purbayanto et al., Phys. Chem. Chem. Phys., 2020, 22, 2010–2018, DOI: ; 10.1039/C9CP05464B .